Disadvantages of red: The color congruence effect in comparative price advertising - Kim, Heejin; Jang, Jung Min (Frontiers in Psychology, 2022)
Based on the metaphorical association of the color, the color red is often considered to be associated with a “hot deal” in price promotion context. This has led to the popular use of the color red in promotions in the marketplace. This study challenges the lay belief, that the color red used in price advertising positively influence consumers’ value perception, through 2 studies. Findings from two experiments revealed a contrasting pattern of results depending on the discount depth. In particular, when the discount depth is high, consistent with the lay belief, red color led more favorable responses on the price promotion than other colors (white in study1 and green in study2). On the contrary, when the discount depth is unambiguously low, consumers who were exposed to price promotion advertising with a red background color reported lower value perception compared to those who saw the same advertisement with other colors We attribute this effect to the degree of “processing fluency” that arises from the congruence between color and promotion contents. Our research adds to the existing literatures of color functioning in psychology by showing that the match between the referential meaning of the color red (i.e., a hot deal) in marketing communication.